PENERAPAN MODUL PEMBELAJARAN MATERI LIMBAH MENINGKATKAN KEMAMPUAN LITERASI DASAR SISWA NANGA UBAT - Gracella, Elsi; Wedyawati, Nelly (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2025)
The use of modules in education for children in remote areas has many benefits, especially for increasing literacy skills. Literacy ability refers to a person's ability to read, understand, interpret, evaluate, and use written information in various contexts. Literacy includes not only the ability to read and write, but also an in-depth understanding of texts, critical thinking skills, and effective communication skills. The purpose of this research is to improve students' literacy skills, especially reading and writing skills, by using learning modules. In carrying out research researchers used a qualitative approach. Results student changes were so clear that there were some students who experienced rapid increases and there were students whose changes were only slight.